PENGARUH KEPEMIMPINAN DAN KESEJAHTERAAN TERHADAP KINERJA TENAGA ADMINISTRASI DI PERGURUAN TINGGI - Muhammad, Muhammad (MPI STAI Sangatta Kutai Timur, 2023)
This study was quantitative research. The data collecting technique used questionnaires and documentation. The population in this study were permanent administration staff in STAI Sangatta total of 16. The hypothesis test used double linearity regression, t partial test, and F simultaneous test. This study revealed that: 1) there were positive impacts on leadership significantly on administration staffs’ performance in STAI Sangatta, this case was proved by thitung > ttabel (3.323 > 2.051) with a significant level of 0.027 ≤ 0.05.2. There were no positive impacts and welfare significantly on administration staff performance in STAI Sangatta, it was proved by thitung < ttabel (1.083 < 2.015) with a significant level of 0.288<0.05.3. There were no significant positive impacts on leadership and welfare of administration staff’s performance in STAI Sangatta. It was proved by Fhitung < Ftabel (2.675 < 3.33) with a determinant coefficient of 0.160. it meant its impact of 16% in a very low category. While 84% had been influenced by other factors. The conclusion of this study leadership and welfare did not significantly influence the administration staff’s performance in STAI Sangatta East Kutai simultaneously.